Manajemen Pendidikan Al-Qur’an Jami’atul Qurro’ Palembang - Agung Kurniawan (Studia Manageria, 1970)
The purpose of this study was to determine the planning, implementation, supervision and funding of education implemented by the Al-Qur'an Jami'atul Qurro Islamic Boarding School (PPAJQ) Palembang. The method used in this study is a qualitative descriptive research method with a study caseapproach. Data collection techniques using the method of observation, documentation, and interviews. Research information was obtained from the mudir (leader), boarding school administrators, teaching staff and some students. The data obtained were analyzed with descriptive analysis that is describing the planning, implementation, supervision, evaluation and funding of Education. The results of this study are: (1) education planning that is implemented is made by the fields that have been determined not fully running wellyet, (2) the implementation of education implemented by PPAJQ is not only baseline and tahfidz education but there are several methods applied including the following: applying formal education outside the hut, imposing non-formal education, boarding school, providing skills education, applying education throughout the day, applying the pesantren curriculum, (3) supervisingoftheeducation is carried out throughout the school but only pesantren who are in control direct the course of programs that have been planned and assisted with the asatidz council, (4) educational funding is sourced from SPP, donors, an-Nahla hadroh album sales and local government.